Orthodromic transposition of the temporal muscle for facial paralysis: Made easy and better - Viterbo, Fausto [UNESP]; Faleiros, HRD (Lippincott Williams & Wilkins, 2005)
The authors present a modified technique of transposition of temporal muscle for reanimation of facial paralysis. Fourteen cases illustrate the simplicity, advantages, and excellent esthetic and functional results of this method.
Keywords: facial palsy; temporal muscle; flap; orthodromic